Message in a bottle - Malcolm, Jahnna N. (New York : Simon Pulse, 2005)
Quinn decides fate has played a hand when she finds a bottle washed up on the beach that contains a note written nine years earlier by the same hunky guy she met just the night before, but their relationship gets off to a bad start when Quinn leads the wealthy Dash to believe she is his social equal.
Young Adult
Young Adult
Kliatt
Keywords: Man-woman relationships -- Fiction; Dating (Social customs) -- Fiction; Beaches -- Fiction; Love -- Fiction; Man-woman relationship -- Fiction; Dating (Social customs) -- Fiction; Beaches -- Fiction; Love stories